THE EFFECT OF ANGER MANAGEMENT TRAINING TOWARD AGGRESSIVE BEHAVIOR IN ADOLESCENTS - Farisandy, Ellyana Dwi; Hartini, Nurul (Jurnal Psikologi, 2020)
The purpose of this study is to examine the effect of anger management training on adolescent aggression behavior. This study uses a quasi-experimental method, with one group pretest-posttest design. The treatment is only given to one group. The population of this study is 15 male neglected  and street adolescences. The subjects of this study were six male adolescences (Mage = 14 years old, SD =.75), with highly aggressive behavior. Aggression behavior is measured using the CBCL (Child Behavior Checklist). The adolescence who have scores above the threshold line are then involved in this study. Data were collected before and after the intervention using the Aggression Questionnaire (AQ) (29 items, α = .917). As a treatment, a nine-session of anger management training was conducted. The data was analyzed with the Wilcoxon signed-rank test, and the result shows that there is a significant difference knowledge before and after training (p = .028, p <.05). Posttest scores were better than pretest scores. It can be concluded that anger management training can be considered as a good program in increasing knowledge about aggression and procedure in reducing aggressive behavior.